Análise do financiamento de empreendimentos sociais: o uso de blockchain e criptomoedas por uma fintech de impacto social - Loiola, Ricardo Alan Kardec (2019)
Technological advancements such as artificial intelligence (AI), Blockchain, biometrics, and robotics, should become a trend, challenging conventional thinking about how to interact and deliver profitable banking products and services while providing development and innovation and social transformation. Taking into consideration this context, by identifying a Fintech with an ecosystem that focuses on social impact investments using Blockchain technology and the international liquidity of cryptocurrencies, this study has the purpose of identifying how a social business venture makes use of Blockchain tools to promote social innovation using the social innovation conceptual model by Tardif and Harrisson (2005) from an analytical framework with suggested new dimensions. This is an exploratory and descriptive study of qualitative nature, using case studies as a research strategy, through data field collection, semi-structured interviews, direct observation, and document analysis. Data were analyzed using the content analysis technique, in which categories and subcategories of analysis, aligned with the proposed specific objectives and with the adopted theoretical framework, served as a criterion for the decomposition and analysis of the collected contents, operationalized in the ATLAS.ti software. The results identified some identity miscegenation relationships, values, and norms among the stakeholders, emphasizing group learning, new practices, knowledge, and skillsets. It was also identified new configurations that reflect improvements through the highlighted social practices. The results show that the partnership models among the players involved facilitated social innovation, developed an appreciation, in this context, for labor, for the achievement of financial autonomy and the regional economic development of impact. Credit access using Blockchain technology is an alternative to meet demands, strengthening the organization and mobilization of social players in excluded territories, fostering entrepreneurship, transformation, and social impact scaling.